Macroeconomic imbalances - Spain (Luxembourg, 2012)
"On 14 February 2012, the European Commission presented its first Alert Mechanism Report (AMR) in accordance with the Regulation (EU) No. 1176/2011 on the prevention and correction of macroeconomic imbalances. The AMR serves as an initial screening device to identify Member States that warrant further in depth analysis into whether imbalances exist or risk emerging. According to Article 5 of Regulation No. 1176/2011, these country-specific “in-depth reviews” should examine the nature, origin and severity of macroeconomic developments in the Member State concerned, which constitute, or could lead to, imbalances. On the basis of this analysis, the Commission concludes whether it considers that an imbalance exists or not, and if so whether it is excessive or not, and what type of follow-up it will recommend to the Council to address to the Member State.